Basic control principles of omnidirectional wireless power transfer - Zhang,C; Lin,D; Hui,SY (IEEE Transactions on Power Electronics, 2016)
This paper presents the basic control principles of omnidirectional wireless power transfer (WPT) based on the current amplitude control. The principles involve 1) an “omnidirectional” scanning process for detecting the power requirements in a 3-D space and 2) a “directional” power flow control for focusing the wireless power toward the targeted areas. Such principles apply to any WPT system comprising three orthogonal transmitter coils and multiple receivers with coil resonators. A current amplitude control method capable of generating a magnetic vector at a set of points evenly distributed on a spherical surface is explained. Based on the voltage and the current information in the transmitter circuit, the power involved in each vector over the spherical surface can be obtained. By scanning the vector over the spherical surface, the collective power flow requirements for the targeted loads can be determined. Based on the power requirements for the vectors over the spherical surface, a weighted time-sharing scheme is adopted to focus the wireless power toward the targeted areas. This method has been successfully applied to a hardware prototype. Both theoretical and experimental results are included to confirm these principles.